'Coelum non animum mutant qui trans mare currunt': David Stradling (1537–c.1595) and His Circle of Welsh Catholic Exiles in Continental Europe. Issue 2 (17th October 2014) - Orofino, Anna Maria
Abstract : This paper examines the lives and careers of two Welsh Catholics, David Stradling and Hugh Owen, who sought refuge on the Continent during the reign of Elizabeth I. Whereas something about Hugh Owen's life is known, particularly of his career as the creator of an intelligence service which countered that of Sir Francis Walsingham, David Stradling's life has, in contrast, remained somewhat obscure. Little is known of him other than some details of his family background and his education. My recent research at the Simancas Archive and at the Archives Royales de Bruxelles, however, has revealed hitherto unknown sources that now provide further information on both men. In describing the events of their flight from England to the Continent and their establishment there, I re-examine the circle of well-known English Catholic refugees in the Spanish Low Countries and in Spain.